COMPARATIVE ANALYIS OF LINGUISTIC FACTORS SHAPING PRAGMATIC MEANING IN ENGLISH AND UZBEK LANGUAGES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Pragmatics is a branch of linguistics that focuses on how language is used in context, examining a variety of context-dependent aspects of communication. It explores how the meaning of words and phrases shifts depending on the situation, the participants, and the purpose of the communication. Pragmatics studies not only the literal meaning of words but also the implied meanings that arise from the context in which they are spoken.For example, the same phrase can convey different meanings depending on the situation. A statement like "The weather is so beautiful" could be a simple observation or an indirect suggestion to go outside. Pragmatics also looks at the social conventions in communication, such as how respect, equality, or social hierarchy affect interactions. It includes the examination of implicit meanings—those that are not directly stated but understood based on context. For instance, when someone says, "The weather is so beautiful," they may be suggesting a course of action rather than merely commenting on the weather. Pragmatic meaning goes beyond the literal interpretation of words, encompassing context, social norms, cultural expectations, and speaker intent. Linguistic elements provide the foundation for conveying meaning, while contextual factors enrich interpretation by providing additional layers of context and nuance. By considering both linguistic and contextual cues, communicators can navigate the complexities of language use and achieve effective communication in diverse contexts. Linguistic factors refer to the linguistic elements and structures that contribute to pragmatic meaning interpretation.